Influence of drainage and nutrient-solution nitrogen and potassium concentrations on the agronomic behavior of bell-pepper plants cultivated in a substrate - Wamser, Anderson Fernando; Cecilio Filho, Arthur Bemardes [UNESP]; Dalmazzo Nowaki, Rodrigo Hiyoshi [UNESP]; Mendoza-Cortez, Juan Waldir; Urrestarazu, Miguel (Public Library Science, 2017)
The interactive effects of N (6, 9, 12 and 15 mmol L-1) and K (3, 5, 7, and 9 mmol L-1) concentrations in nutrient solutions were evaluated on bell pepper grown in a coconut-coir substrate and fertilized without drainage. An additional treatment with drainage was evaluated using N and K concentrations of 12 and 7 mmol L-1, respectively. The hybrid Eppo cultivar of yellow bell pepper was cultivated for 252 days beginning 9 November 2012. Electrical conductivity (EC), the N and K concentrations in the substrate solution, marketable fruit yield, total dry weight and macronutrient concentrations in shoots were periodically evaluated. Fruit production was lower in the system without drainage, regardless of the N and K concentrations, compared to the recommended 10-20% drainage of the volume of nutrient solution applied. Higher K concentrations in the nutrient solution did not affect plant production in the system without drainage for the substrate with an initial K concentration of 331.3 mg L-1. Fruit yield was higher without drainage at a nutrient-solution N concentration of 10.7 mmol L-1. The upper EC limit of the substrate solution in the system without drainage was exceeded 181 days after planting. Either lower nutrient concentrations in the nutrient solution or a drainage system could thus control the EC in the substrate solution.